Diagnostic Utility of Immunohistochemical Expression of HE4 in Epithelial Ovarian Neoplasm: A Cross-sectional Prospective Study - Nahar, Begum Afrin; Saha, Rama; Das, Chhanda; Kamilya, Gourishankar (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Background: Mortality in case of ovarian malignancy is high due to late diagnosis. Early and accurate diagnosis can improve the case specific management. Ovarian carcinoma has the highest mortality rate among all gynaecological malignancies. HE4 (human epididymis protein 4) which is proved to be over expressed in the ovarian cancer cells, is considered a new biomarker for ovarian cancer diagnosis . Aims and Objectives: The study was undertaken to evaluate the immunohistochemical expression of HE4 in various epithelial ovarian neoplasm. Material and Methods: It was a cross sectional, prospective, single institution based study, conducted in the department of Pathology in collaboration with the department of Gynaecology and Obstetrics, from December 2016 to January 2019 in our institution. A total 71 cases were selected for this study. Results: Serous tumour was the most common epithelial tumour followed by mucinous tumour. Highest percentage of expression of HE4 was seen in high grade serous cancer and malignant endometrioid tumour. Benign serous and mucinous tumour shows negative expression mostly. We found statistically significant correlation between HE4 expression and different types of epithelial ovarian tumours (p=0.000). Conclusions: HE4 was highly expressed in malignant ovarian tumour especially serous and endometrioid carcinoma and can be used as an important biomarker for malignant ovarian neoplasm. Expression in high grade ovarian serous cancer support its prognostic value also.